2014
DOI: 10.1590/1807-1929/agriambi.v18n12p1228-1234
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e produção de manjericão em sistema hidropônico NFT sob salinidade

Abstract: R E S U M ONo semiárido brasileiro a falta de água de boa qualidade tem justificado o desenvolvimento de pesquisas científicas no aproveitamento de águas salobras. No presente trabalho avaliaram-se os efeitos de águas salobras em relação ao crescimento e à produção de plantas de manjericão em hidroponia, de outubro a novembro de 2012. Os tratamentos consistiram de quatro níveis de salinidade da água (1,45; 3,80; 6,08 ), respectivamente; não ocorreu diferença entre águas isosmóticas de NaCl e rejeito de dessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
29
4
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 16 publications
10
29
4
15
Order By: Relevance
“…These results agree with those of Bione et al (2014), who observed linear reduction of 2.09% per unit increase of salinity in basil plants under hydroponic cultivation and, therefore, a reduction much lower than that obtained in the present study. This difference in the response of the crop to salinity for the variable plant height can be attributed to the adopted cultivation system, since in the hydroponic cultivation the plants tend to increase their tolerance to salinity.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These results agree with those of Bione et al (2014), who observed linear reduction of 2.09% per unit increase of salinity in basil plants under hydroponic cultivation and, therefore, a reduction much lower than that obtained in the present study. This difference in the response of the crop to salinity for the variable plant height can be attributed to the adopted cultivation system, since in the hydroponic cultivation the plants tend to increase their tolerance to salinity.…”
Section: Resultssupporting
confidence: 92%
“…These results confirm those obtained by Bione et al (2014) and Attia et al (2011), who also observed that basil growth was significantly affected by salinity. Figure 1 shows the results referring to the effect of salinity on the variables stem diameter, plant height, number of stems, number of leaves and leaf area.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Leaf fresh matter (LFM), leaf dry matter (LDM) and leaf water content (LWC) and leaf area (LA) were significantly affected by salinity **Significant at 0.01 probability level by F test ( Table 2). The variable leaf water content (LWC) showed the lowest percent reduction (1.7%) for each unit increase in the electrical conductivity of the irrigation water ( Figure 1E); the other variables, LFM, LDM and LA showed reductions of 8.5, 4.3 and 13.4%, respectively, when irrigation water salinity increased by 1 dS m -1 ( Figure 1C, 1D, 1F Some studies confirmed the negative effect of salinity on leaf dry matter and leaf area in watermelon (Martins et al, 2013); dry matter, plant height and number of leaves, in maize (Akbari et al, 2015); plant height, stem diameter, number of leaves, leaf area and leaf dry matter, in eggplant (Lima et al, 2015) and water content, shoot fresh matter and shoot dry matter, in basil (Bione et al, 2014).…”
Section: Resultsmentioning
confidence: 89%
“…A few promising results have been achieved for the rational use of brackish water in the Nutrient Film Technique (NFT) hydroponic system (Santos et al, 2010(Santos et al, , 2011Soares et al, 2010Soares et al, , 2015Alves et al, 2011;Paulus et al, 2012;Bione et al, 2014;Lira et al, 2015), which can open a new perspective for hydroponics as an economic alternative, provided that brackish water is available. In Brazil, the main focus of these studies is the semiarid region, where brackish water is relatively frequent in the underground reserves, for constituting one of the main causes of abandonment of the various wells drilled with public or private resources (Santos et al, 2010).…”
Section: Introductionmentioning
confidence: 99%